The role and status of drama in spiritual and material culture - Qi, Mengrui (Linguistics and Culture Review, 2021)
The relevance of the work is determined by the fact that the full development of society is possible only on the condition that dramatic changes occur in it. The basis for changes in any society is both culture and the motives that flow into culture in order to realise the factors of social formation as much as possible. We believe that culture and its development are possible if there are phenomena in society when an individual rethinks each aspect of his being. Consequently, the role of drama not only as an artistic device in literature, but also as a social phenomenon, has its own direction and significance for a number of projects for the development of both the individual and the social environment as a whole. The novelty of the study is the assertion that each aspect of the implementation of the drama forms, first of all, a response phenomenon that fully manifests itself both in the course of personal experience and in the formation of individual forms of material culture. The authors of the article show the way to form attitude to spiritual and material cultures on the basis of personal dramatic experience.